WP:NOT, WP:NPOV, and Other Stories Wikipedia Tells Us: A Feminist Critique of Wikipedia's Epistemology. (May 2021) - Menking, Amanda; Rosenberg, Jon
Wikipedia has become increasingly prominent in online search results, serving as an initial path for the public to access "facts, " and lending plausibility to its autobiographical claim to be "the sum of all human knowledge." However, this self-conception elides Wikipedia's role as the world's largest online site of encyclopedic knowledge production. A repository for established facts, Wikipedia is also a social space in which the facts themselves are decided. As a community, Wikipedia is guided by the five pillars—principles that inform and undergird the prevailing epistemic and social norms and practices for Wikipedia participation and contributions. We contend these pillars lend structural support to and help entrench Wikipedia's gender gap as well as its lack of diversity in both participation and content. In upholding these pillars, Wikipedians may unknowingly undermine otherwise reasonable calls for inclusivity, subsequently reproducing systemic biases. We propose an alternative set of pillars developed through the lens of feminist epistemology, drawing on Lorraine Code's notion of epistemic responsibility and Helen Longino's notion of procedural objectivity . Our aim is not only to reduce bias, but also to make Wikipedia a more robust, reliable, and transparent site for knowledge production.